Transcriptome analysis provides new ideas for studying the regulation of glucose-induced lignin biosynthesis in pear calli - Yuru Jiao; Xin Gong; Kaijie Qi; Zhihua Xie; Yanling Wang; Kaili Yuan; Qi Pan; Shaoling Zhang; Katsuhiro Shiratake; Shahrokh Khanizadeh; Shutian Tao (BMC Plant Biology, 2022)
Abstract Background Glucose can be involved in metabolic activities as a structural substance or signaling molecule and plays an important regulatory role in fruit development. Glucose metabolism is closely related to the phenylpropanoid pathway, but the specific role of glucose in regulating lignin biosynthesis in pear fruit is still unclear. The transcriptome of pear calli generated from fruit and treated with glucose was analyzed to investigate the role of glucose in lignin biosynthesis. Results The treatment of exogenous glucose significantly enhanced the accumulation of lignin in pear calli. A total of 6566 differentially expressed genes were obtained by transcriptome sequencing. Glycolysis was found to be the pathway with significant changes. Many differentially expressed genes were enriched in secondary metabolic pathways, especially the phenylpropanoid pathway. Expression of structural genes (PbPAL, PbHCT, PbCOMT, PbPRX) in lignin biosynthesis was up-regulated after glucose treatment. In addition, glucose might regulate lignin biosynthesis through interactions with ABA, GA, and SA signaling. Several candidate MYB transcription factors involved in glucose-induced lignin biosynthesis have also been revealed. The qRT-PCR analyses showed that the expression pattern of PbPFP at early developmental stage in ‘Dangshansuli’ fruits was consistent with the trend of lignin content. Transient expression of PbPFP resulted in a significant increase of lignin content in ‘Dangshansuli’ fruits at 35 days after full bloom (DAB) and tobacco leaves, indicating that PbPFP (Pbr015118.1) might be associated with the enhancement of lignin biosynthesis in response to glucose treatment. Conclusions PbPFP plays a positive role in regulating lignin biosynthesis in response to glucose treatment. This study may reveal the regulatory pathway related to lignin accumulation in pear calli induced by glucose.